A plant virus protein, NIa-pro, interacts with Indole-3-acetic acid-amido synthetase, whose levels positively correlate with disease severity - Gnanasekaran, Prabu; Zhai, Ying; Kamal, Hira; Smertenko, Andrei; Pappu, Hanu R. (Frontiers in Plant Science, 2023)
Potato virus Y (PVY) is an economically important plant pathogen that reduces the productivity of several host plants. To develop PVY-resistant cultivars, it is essential to identify the plant-PVY interactome and decipher the biological significance of those molecular interactions. We performed a yeast two-hybrid (Y2H) screen of Nicotiana benthamiana cDNA library using PVY-encoded NIa-pro as the bait. The N. benthamiana Indole-3-acetic acid-amido synthetase (IAAS) was identified as an interactor of NIa-pro protein. The interaction was confirmed via targeted Y2H and bimolecular fluorescence complementation (BiFC) assays. NIa-pro interacts with IAAS protein and consequently increasing the stability of IAAS protein. Also, the subcellular localization of both NIa-pro and IAAS protein in the nucleus and cytosol was demonstrated. IAAS By converts converting free (active) IAA (active form) to the conjugated IAA (inactive form), IAAS inactive, conjugated form which plays a crucial regulatory role in auxin signaling. Transient silencing of IAAS in N. benthamiana plants interfered withreduced the PVY-mediated symptom induction and virus accumulation. Conversely, overexpression of IAAS enhanced symptom induction and virus accumulation in infected plants. In addition, the expression of auxin-responsive genes was found to be downregulated during PVY infection. Our findings demonstrate that PVY NIa-pro protein potentially promotes disease development via modulating auxin homeostasis.